Nancy Drew and the clue crew dance off - Keene, Carolyn; Pamintuan, Macky (Aladdin New York, 2011)
Kids Can Dance!, the famous reality TV show, is holding auditions at River Heights Elementary. Nancy and her friends are all eager to try out, and meet the famous host Bryce Brown. But when something goes wrong with every dancers' equipment, music, or routine, could someone be trying to ruin the River Heights tryouts? Nancy Drew and the Clue Crew are on the case!